2012
DOI: 10.1037/a0026215
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and qualitative changes in encoding strategy with experience: Evidence from the test-expectancy paradigm.

Abstract: Three experiments demonstrated learners’ abilities to adaptively and qualitatively accommodate their encoding strategies to the demands of an upcoming test. Stimuli were word pairs. In Experiment 1, test expectancy was induced for either cued recall (of targets given cues) or free recall (of targets only) across 4 study–test cycles of the same test format, followed by a final critical cycle featuring either the expected or the unexpected test format. For final tests of both cued and free recall, participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 127 publications
(148 reference statements)
2
76
0
1
Order By: Relevance
“…We did not, however, find evidence in support of deWinstanley and Bjork's suggestion that actually experiencing the memorial advantage of generation in the context of a test is necessary for the development of an improved encoding strategy for future to-be-read information. Rather, our pattern of results seems more consistent with the enhanced contextualprocessing account suggested by Bjork and Storm (2011) and, more generally, with test-expectancy findings, such as those of Finley and Benjamin (2012). Namely, that for new information to be encoded with a more effective processing strategy, learners need to be made aware of the type of test they will be receiving and the type of information to which such a test is sensitive-that is, the type of information one needs to encode during study to perform well on such a test.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We did not, however, find evidence in support of deWinstanley and Bjork's suggestion that actually experiencing the memorial advantage of generation in the context of a test is necessary for the development of an improved encoding strategy for future to-be-read information. Rather, our pattern of results seems more consistent with the enhanced contextualprocessing account suggested by Bjork and Storm (2011) and, more generally, with test-expectancy findings, such as those of Finley and Benjamin (2012). Namely, that for new information to be encoded with a more effective processing strategy, learners need to be made aware of the type of test they will be receiving and the type of information to which such a test is sensitive-that is, the type of information one needs to encode during study to perform well on such a test.…”
Section: Discussionsupporting
confidence: 89%
“…Experience with practice tests also provides students with the chance to learn the format of future exams and to adjust their study strategies accordingly. As Finley and Benjamin (2012) argued, studying is most efficient when learners are equipped with beneficial encoding strategies.…”
Section: Discussionmentioning
confidence: 99%
“…This task entails different cognitive demands than free recall. Finley and Benjamin (2012) showed that subjects who expect such a cued-recall test do much better on it than do subjects who expect free recall, and vice versa. The researchers also showed that these differences were related to test-appropriate changes in the strategies adopted by their subjects as they became better at one of the tasks.…”
Section: Empirical Evidencementioning
confidence: 98%
“…Not only do learners consider individual items' characteristics (e.g., Mueller et al, 2013), they also analytically consider multiple relations among studied items and the interaction between these relations and expected test format. Few studies have shown that expected test format affects the accuracy of metacognitive monitoring (Finley & Benjamin, 2012;Thiede, 1996). While much research has shown that relatedness plays a large role in multiple areas of cognition, the current studies show that learners' predictions about the influences of relatedness are incredibly accurate under various testing circumstances.…”
Section: Discussionmentioning
confidence: 50%
“…Learners may consider the expected test format (and its match with how they are encoding and rehearsing the stimuli) when assigning JOLs and give ratings based upon how well their output strategy aligns with the test format. Prior research supports this idea, as expected test format has an impact on student's mnemonic predictions (and consequently their study choices; Finley & Benjamin, 2012;Thiede, 1996;Thiede, Wiley, & Griffin, 2011). We investigated these three different explanations across two experiments.…”
Section: Monitoring Relatednessmentioning
confidence: 75%